Integrating Lipidomics and Transcriptomics Reveals the Crosstalk Between Oxidative Stress and Neuroinflammation in Central Nervous System Demyelination - Zhao, Zhi-jie; Zheng, Rui-zhe; Wang, Xiao-jing; Li, Tong-qi; Dong, Xiao-hua; Zhao, Chang-yi; Li, Xin-yuan (Frontiers in Aging Neuroscience, 2022)
Multiple sclerosis (MS) is an incurable and progressive neurodegenerative disease that affects more than 2.5 million people worldwide and brings tremendous economic pressures to society. However, the pathophysiology of MS is still not fully elucidated, and there is no effective treatment. Demyelination is thought to be the primary pathophysiological alteration in MS, and our previous study found abnormal lipid metabolism in the demyelinated corpus callosum. Growing evidence indicates that central nervous system (CNS) demyelinating diseases never result from one independent factor, and the simultaneous participation of abnormal lipid metabolism, oxidative stress, and neuroinflammation could potentiate each other in the pathogenesis of MS. Therefore, a single omics analysis cannot provide a full description of any neurodegenerative disease. It has been demonstrated that oxidative stress and neuroinflammation are two reciprocal causative reasons for the progression of MS disease. However, the potential crosstalk between oxidative stress and neuroinflammation remains elusive so far. With an integrated analysis of targeted lipidomics and transcriptomics, our research presents the potential interaction between abnormalities of lipid metabolism, mitochondrial dysfunction, oxidative stress, and neuroinflammation in CNS demyelinating diseases. The findings of this paper may be used to identify possible targets for the therapy of CNS demyelinating diseases.